2010
DOI: 10.1051/fruits/2009036
|View full text |Cite
|
Sign up to set email alerts
|

Comparaison de l'efficacité de deux méthodes de multiplication rapide de plants de bananier à partir de l'étude des caractéristiques agronomiques d'un hybride de bananier plantain (Musaspp.)

Abstract: Comparison of the effectiveness of two vegetative propagation methods for banana trees from the study of the agronomic characteristics of a hybrid of plantain (Musa spp.). Abstract-Introduction. The objective of our study was to evaluate the agronomic performance of plantain hybrid plants (CRBP-39, Musa cv. AAAB) obtained through two vegetative propagation methods: in vitro culture, called the "CIV technique", and a newly developed technique of plants derived from stem bits, called the "PIF technique". The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
(5 reference statements)
0
4
0
1
Order By: Relevance
“…Plants were maintained and multiplied in the tropical greenhouse (greenhouse no. 13; G2) using the PIF ( Plants Issus de Fragments de tiges , Plants from Stem Fragments) technique (Kwa 2003, 2009, Meutchieye 2009, Sadom et al 2010, Mbunzu et al 2019). Plants were irrigated daily, until they reached 40–60 days of age (4–6 leaf stage), for their use in all tests.…”
Section: Methodsmentioning
confidence: 99%
“…Plants were maintained and multiplied in the tropical greenhouse (greenhouse no. 13; G2) using the PIF ( Plants Issus de Fragments de tiges , Plants from Stem Fragments) technique (Kwa 2003, 2009, Meutchieye 2009, Sadom et al 2010, Mbunzu et al 2019). Plants were irrigated daily, until they reached 40–60 days of age (4–6 leaf stage), for their use in all tests.…”
Section: Methodsmentioning
confidence: 99%
“…This result highlights that particular attention should be paid to the sanitary state of the plant material used during plantain plantation for ensuring plantation durability. In this sense, it has been already observed that the use of healthy plants, obtained through the PIF technique (Lefranc et al, 2010;Sadom et al, 2010), significantly reduced pest infestations at the beginning of the plantation (Loranger-Merciris et al, 2022). In contrast, the higher density of H. multicinctus observed in agroecological perennial banana plantations showed that these ectoparasite nematodes are more persistent in more organic cropping systems.…”
Section: Cropping Systems Pests and Plant Healthmentioning
confidence: 90%
“…The plants were identi ed and collected from peasant plantations in the province of South Kivu in (Democratic Republic of Congo), with the support of the International Institute of Tropical Agriculture-IITA/Kalambo (Bukavu, DR Congo), in accordance with 39 , then certi ed by the Plant Clinic of the 'Agro Louvain-Services' platform (located in the plant pathology laboratory of the Université catholique de Louvain, Louvain-la-Neuve, Belgium). As transmission of the virus by mechanical inoculation has never been successful 40,41 , all the plants used including the healthy ones were maintained and propagated in the tropical greenhouse (greenhouse n°13; G2) of the UCLouvain (Louvain-la-Neuve, Belgium) using the PIF technique (Plants from Stem Fragments) [42][43][44][45][46] and were irrigated daily, until they reached 40-60 days of age (4-6 leaf stage), for their use in aphid rearing, as well as for viruliferous and non-viruliferous alate aphid attractiveness tests. Severe symptoms of BBTV were observed for plants obtained directly by the PIF technique from infected banana bulbs, since offspring from an infected strain are automatically infected and show severe symptoms of BBTV 47,48 .…”
Section: Introductionmentioning
confidence: 99%